2020
DOI: 10.1016/j.surg.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Is a “COVID-19-free” hospital the answer to resuming elective surgery during the current pandemic? Results from the first available prospective study

Abstract: Background Resumption of elective surgery during the current coronavirus disease 2019 pandemic crisis has been debated widely and largely discouraged. The aim of this prospective cohort study was to assess the feasibility of resuming elective operations during the current and possible future peaks of this coronavirus disease 2019 pandemic. Methods We collected data during the peak of the current pandemic in the United Kingdom on adult patients who underwent elective sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 8 publications
1
26
0
6
Order By: Relevance
“…Ferenczi et al [ 17 ], from Virginia Medical Center, tested 840 patients during the preoperative period with 3 positive tests that were rescheduled, demonstrating the utility of preoperative screening as a safe way to prevent surgery in asymptomatic COVID patients. Gammeri et al [ 22 ] reported excellent results of performing RT-PCR tests for every patient scheduled for surgery during the outbreak in the UK at a COVID-19-free hospital. Of the 309 patients operated on, no one had COVID-19 infection, but at least 1 patient had a positive test.…”
Section: Discussionmentioning
confidence: 99%
“…Ferenczi et al [ 17 ], from Virginia Medical Center, tested 840 patients during the preoperative period with 3 positive tests that were rescheduled, demonstrating the utility of preoperative screening as a safe way to prevent surgery in asymptomatic COVID patients. Gammeri et al [ 22 ] reported excellent results of performing RT-PCR tests for every patient scheduled for surgery during the outbreak in the UK at a COVID-19-free hospital. Of the 309 patients operated on, no one had COVID-19 infection, but at least 1 patient had a positive test.…”
Section: Discussionmentioning
confidence: 99%
“…A recent UK-based study by Gammeri et al 32 reported on 309 NHS patients who underwent planned surgery at a COVID-free independent sector hospital. Like the present study, there were no adverse outcomes and no mortality within 30 days of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Like the present study, there were no adverse outcomes and no mortality within 30 days of surgery. However, the patient cohort was different: Gammeri et al 32 only performed surgery on low-risk patients undergoing procedures that could be performed as day cases or within 23 hour stays. Our study presents a simple method to prioritize patients, based on the FSSA procedural guide and incorporating additional biopsychosocial factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the COVID status of the patient is known, they can be allocated to either a ‘COVID positive’ ward or a ‘COVID free’ ward and then their surgery can be managed appropriately with the correct level of PPE. A UK study showed that using ‘COVID-19 free’ hospitals, where the patients were neither suspected nor proven to be infected with SARS-CoV-2 virus, enabled safe elective surgery to proceed without serious adverse outcomes [ 4 ]. ‘COVID-free’ areas may indeed be paramount to ensuring that safe surgery may continue without complications due to COVID-19.…”
mentioning
confidence: 99%